The effect of cognitive conflict schemes strategy on conceptual change in the art of acting among students of the Institute of Fine Arts (Journal of the College of Basic Education, 2022)
The current research aims to identify the effect of the cognitive conflict schemes strategy on conceptual change in the art of acting among students of the Institute of Fine Arts, in addition to the research problem, its importance and the limits of the research. Constructivist theory, conceptual change, the strategy of cognitive conflict schemas and the art of representation in addition to previous studies and their discussion. In the third chapter, the research procedures, as the researcher adopted the experimental method, quasi-experimental design, society, sample, research tool, honesty, stability and application, in addition to statistical methods, and the fourth chapter concluded that there is a significant impact on the strategy of conflict schemas. Cognitive change in conceptual change in the art of representation, then conclusions, recommendations and suggestions, then a list of sources and supplements.